The Response to Fishing Decisions and Changes in Fishing Income during Extreme Weather: A Behavioural Economy Study of Small-Scale Coastal Fisher Households - Rahim, Abd.; Abdul Malik; Diah Retno Dwi Hastuti (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research 1. Fishermen continue fishing during extreme weather despite higher risks and reduced income to sustain their households. 2. Fishing decisions are influenced by education, engine power, and income potential, while experience and family size have less impact. 3. Fishing income declines significantly in extreme weather, with fuel costs being the main factor affecting profits. 4. Adaptation strategies include income diversification, adjusting fishing locations, and modifying gear to cope with climate uncertainties. 5. Policies should support climate adaptation, financial security, and alternative livelihoods for small-scale fishing communities. Abstract Extreme weather, attributed to global climate change, has altered the economic behaviour of small-scale fishing households in coastal areas. This study aims to analyse the economic behaviour of fishermen by investigating their fishing decisions using a logistic regression model using the maximum likelihood estimation method and their fishing business income through a normalized profit function. The research employed a quantitative research method with a survey approach conducted in the western coastal region of Barru Regency, Indonesia. The research sample consisted of 209 fishing households. The findings reveal that fishermen fish during extreme weather conditions to meet their household's economic needs, even though their earnings are diminished. Various factors, including the power of the boat engine, fishermen's age and education level, and the potential income from fishing, influence the decision to fish during extreme weather. Additionally, engine fuel prices, education levels, and the number of dependents in the family also impact fishers' income during extreme weather. The most important factor influencing the decision to fish in extreme weather conditions is formal education. Another factor that has the greatest impact on fishermen's income, both in the fishing season and during extreme weather, is the price of engine fuel. Fishermen can adapt to events triggered by extreme weather by implementing specific strategies. For instance, diversifying income by aquaculture production can be an alternative to sea fishing. Diversifying the types of fishing gear to accommodate different weather conditions is equally crucial. Fishing periods and locations can be adjusted to align with prevailing weather conditions. The contribution and significance of this research is to provide insight and understanding of the impact of extreme weather on fishing decisions and changes in the income of capture fishermen. This condition is the economic behaviour of small-scale fishing households in coastal areas when faced with extreme weather events.